Unveiling the Miracular Aspect of Qur’an on Viruses and Their Wonders: A Descriptive Qualitative Study - Abdillah Kitota (Penerbit Hellow Pustaka, 2024)
Over centuries, viruses have puzzled microbiologists due to their wonders: their sizes, shapes, structures, morphologies, their true nature, their life cycle; and subsequent disease progression, morbidity, and mortality. This descriptive qualitative study adopted Thematic Approach and Synoptic Approach to uncover how Qur'an allude to these wonders. Tafsir Ibn Kathir was used for the preliminary interpretation of the identified verses. Data concerning the wonders of viruses were screened from MEDLINE and PUBMED databases. The preposition مِن (part of) used in the phrase لَا يَعْزُبُ عَنْهُ مِثْقَالُ ذَرَّةٍ فِي السَّمَاوَاتِ وَلَا فِي الْأَرْضِ وَلَا أَصْغَرُ مِن ذَٰلِكَ وَلَا أَكْبَرُ إِلَّا فِي كِتَابٍ مُّبِينٍ (not even the weight of a speck of dust or less than that or greater escapes His knowledge in the heavens or in the earth but it is in a Clear Book) of Qur’an, 61:10, which is similar to another phrase used in Qur’an, 34:3, allude that, even the virus particles and their tiniest particles that makes them, are within Allah’s knowledge. This modest contribution may help people to ponder on the presence, greatness and glory of Allah (S.W.T). May also generate the interest of other scholars to mount further research in this subject.